The Effect of Postpartum Yoga on Increasing Breast Milk Production in Breastfeeding Mothers 0-6 Months - Enggar, Enggar; Sirri, Jein Christanti; Gana, Meissy Trilita; Pont, Anna Veronica (Jurnal Bidan Cerdas, 2025)
Background: Yoga is useful for increasing blood flow to the breasts. Practicing yoga will calm the mother's mind and soul so that oxytocin will be produced more when there is peace of mind and soul and a pleasant and peaceful sensation to increase breast milk production. Objective: This study aimed to investigate the effect of postpartum yoga on breast milk production among breastfeeding mothers aged 0-6 months in the Biromaru Health Center Work Area. Method: This study used a pre-experimental design.in., one.group.'one-group pretest-posttest design. The sample was breastfeeding mothers aged 0-6 months totaling 24 respondents taken through the Purposive sampling technique. The study was conducted in April-July 2022. Data analysis used the Wilcoxon test. Results: research found an increase in breast milk production which is shown by the amount of breast milk production before the implementation of yoga as many as 8 people (33.3%) had insufficient breast milk production (≤60 ml) and as many as 16 people (66.7%) with sufficient breast milk production (>60 ml). After doing yoga as many as 3 people (12.5%) had insufficient breast milk production and as many as 21 people (87.5%) had sufficient breast milk production. The analysis obtained a p-value = 0.001 (p <0.05) to show a significant effect between postpartum yoga and increased breast milk production. Conclusion: breastfeeding mothers can produce more breast milk because they do yoga. "To meet the nutritional needs of children and achieve the goal of exclusive breastfeeding, we hope that breastfeeding mothers can do yoga to increase breast milk production as a safe and simple method.